Hybridization solution of electrical energy demand response and forecasting program by using PSO-LSSVM technique - Ali, Amira Noor Farhanie; Sulaima, Mohamad Fani; Tahir, Musthafah Mohd.; Razak, Intan Azmira Wan Abdul; Kadir, Aida Fazliana Abdul; Rahman, Zulkifli Ab. (2023)
The ever-growing electricity market provides an excellent opportunity for the industrial sector to implement effective energy management through demand response (DR). The demand for poultry meat and eggs is expected to continue increasing with the growing population, leading to higher energy generation costs during peak periods. To overcome this challenge, a demand-side management (DSM) approach is put into action, which involves the use of DR schemes and diverse action strategies. The suggested study will optimize energy savings in the industrial sector and improve the sector's power consumption profile. The study uses a particle swarm optimization (PSO) technique and a least square support vector machine (LSSVM) to forecast short-term load and optimize demand profiles under the Enhance Time of Use (ETOU) tariff scheme. The proposed formulation of the ETOU optimization achieves an energy cost savings of up to 7.57% (PSO) and 7.98% (PSO-LSSVM), and the proposed models are intended to lower the cost of electrical energy usage across all price ranges. The study's findings will assist manufacturers in transitioning to the ETOU tariff and contribute to the national DSM initiative program. Future research may examine other optimization algorithms and load forecasting models to refine ETOU tariff rate price reduction strategies and define available load for specific load management strategies.